Copper Enrichment in Solid with Selective Reverse Leaching with Oxalic Acid - Turan, M. Deniz; Sari, Zeynel Abidin; Erdemoglu, Murat (Springer, 2020)
As the first part of a novel process proposed for copper extraction, selective dissolution of iron from chalcopyrite in oxalic acid solutions with hydrogen peroxide was studied. Despite the fact that both iron and copper are readily soluble in acidic conditions, it was found that oxalic acid provides altered solubility behaviors for these metals. It should be used to form iron (II) oxalate which has a higher solubility (0.008 g/100 g H2O at 293 K) than copper oxalate (2.16x10(-10) g/100 g H2O at 293 K), while hydrogen peroxide was used to provide an oxidative leaching environment to break the chalcopyrite structure. Under the examined leaching conditions where 100 g/L of H2C2O4, 3 M of H2O2, 318 K of leaching temperature, 120 min of leaching time, 25 mL/g of liquid-solid ratio, and 400 rpm of stirring speed were applied, extraction rates of copper and iron from the chalcopyrite concentrate were almost 1.5% and 70%, respectively. Copper was found as a solid oxalate form in the residue obtained after the leaching process in these conditions.
Keywords: Chalcopyrite; Iron dissolution; Oxalic acid; Iron oxalate; Copper oxalate